Brucea javanica oil inhibited the proliferation, migration, and invasion of oral squamous carcinoma by regulated the MTFR2 pathway - Lai, Yihan; Li, Mingkang; Zhan, Juan; Jiang, Lin; Wu, Yuan; Fang, Zhiyi; Zhou, Jianhan; Ma, Yujie; Shao, Yisen; Wang, Wei (Frontiers in Oncology, 2025)
IntroductionOral squamous cell carcinoma (OSCC) is one of the most common malignant tumors in oral and maxillofacial region. The development of new chemotherapy agents and new drug combinations may improve patient survival and quality of life, but both surgery and radiotherapy have significant functional side effects and drug resistance, ultimately resulting in a 5-year survival rate of no more than 60% for OSCC patients. Studies have shown that Brucea javanica oil (BJO) extracts have anti-cancer effects against a variety of cancers, but little research has been reported on OSCC. MethodsCCK8, Colony formation, Scratch test and Transwell invasion assays were applied to determine the effects of BJO on the proliferation, migration, and invasion ability of OSCC cells in vitro. MTFR2 knockdown (shRNA) and overexpression (cDNA) OSCC cells were constructed to evaluate the effect of MTFR2 on the proliferation and invasion of OSCC cells. The nude mouse model of subcutaneous xenograft tumor was used to evaluate the effect of BJO on OSCC cells in vivo. PCR, western blot and immunohistochemistry were used to verify the expression of MTFR2, glycolysis markers and related pathway molecules after BJO treatment.ResultsIn vivo experiments using nude mice with xenografted OSCC cells and in vitro experiments with OSCC cell lines demonstrated that BJO treatment significantly inhibited the proliferation, migration, and invasiveness of OSCC cells. WB and PCR proved that BJO could effectively reduce the expression levels of MTFR2 and SOD2/H2O2 related signal transduction pathways. At the same time, the expression of oxidative phosphorylation markers increased, the expression of glycolytic markers decreased, and glycolysis-mediated decomposition of reactive oxygen species decreased, and H2O2 and oxygen levels decreased.In addition, when MTFR2 expression increased or decreased, SOD2/H2O2 expression also increased or decreased.DiscussionIn this study, we concluded through in vitro and in vivo experiments that BJO may affect the SOD2/H2O2 signaling pathway by down-regulating MTFR2-mediated aerobic glycolysis, thereby inhibiting cell proliferation, Migration, and Invasion. The elucidation of this mechanism helps us to understand the molecular mechanism ofinhibiting OSCC invasion and metastasis by BJO, which has important clinical value or improving the survival rate of OSCC patients.